Design, implementation, and metrological characterization of a wearable, integrated AR-BCI hands-free system for health 4.0 monitoring. (June 2021) - Arpaia, Pasquale; De Benedetto, Egidio; Duraccio, Luigi
Abstract: An integrated real-time monitoring system based on Augmented Reality (AR) and Brain–Computer Interface (BCI) for hands-free acquisition and visualization of remote data is proposed. As a case study, the monitoring of patients' vitals in the operating room (OR) is considered; in particular, through the suitable combination of BCI and AR, the anesthetist can monitor in real-time (through a set of AR glasses), the patient's vitals acquired from the electromedical equipment. Healthcare-related applications are particularly demanding in terms of real-time requirements; hence, the considered scenario represents an interesting and challenging testbed for the proposed system. Experimental tests were carried out at the University Hospital Federico II (Naples, Italy), employing pieces of equipment that are generally available in the OR. After the preliminary functional validation, accuracy and delay were measured, demonstrating the effectiveness and reliability of the proposed AR-BCI-based monitoring system. Graphical abstract: Highlights: AR/BCI-based real-time monitoring system of patient's health. Wireless communication between the monitoring system and the AR Glasses. High wearability with a wireless single-channel BCI. Metrological characterization in terms of transmission accuracy and delay.